Abolish ICE - Uhlmann, Natascha (OR Books, 2019)
"Abuses in detention centers. Detention of handicapped children. The silencing of activists. Each week, another attack on immigrant rights comes to light. It's going to be hard to say we didn't know. ICE has escalated a campaign that tears apart families and ruins lives. But this didn't begin, and won't end, with Donald Trump in the White House. The Obama administration deported record numbers of immigrants, wildly expanded the scope and capacities of ICE, and supported detention center quotas. Voting Democrat alone won't save these children. Immigration does not take place in a vacuum; each time the United States pushes through another exploitative trade deal or wreaks havoc on sovereign countries, we perpetuate migration flows fueled not by opportunity but by desperation. How long will we continue funding an agency premised upon the abuse and dehumanization of undocumented immigrants?We need to abolish ICE. This concise, accessible book sets out the reasons why and the way it can be brought about."--Amazon.com
Keywords: U.S. Immigration and Customs Enforcement.; U.S. Immigration and Customs Enforcement; Central-local government relations -- United States.; Human smuggling -- United States.; Noncitizens -- Government policy -- United States.; Urban policy -- United States.; United States -- Emigration and immigration -- Government policy.; Illegal immigration -- Government policy -- United States.; Noncitizens.; Undocumented Immigrants; Relations gouvernement central-collectivités locales -- États-Unis.; Trafic de migrants -- États-Unis.; Politique urbaine -- États-Unis.; Immigration clandestine -- Politique gouvernementale -- États-Unis.; Immigrants clandestins.; États-Unis -- Émigration et immigration -- Politique gouvernementale.; Human Rights.; POLITICAL SCIENCE.; Corruption & Misconduct.; Noncitizens; Central-local government relations; Emigration and immigration -- Government policy; Human smuggling; Noncitizens -- Government policy; Urban policy; United States; Electronic books.